2003
DOI: 10.1016/s0959-8049(03)00540-9
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variability between general and expert pathologists during the histopathological assessment of large-core needle and open biopsies of non-palpable breast lesions

Abstract: The purpose of this study was to assess whether general pathologists are able to make as accurate and reproducible a diagnosis on large-core needle biopsies as on open breast biopsy specimens. A total of 688 patients underwent a stereotactic large-core (14G) needle biopsy and subsequent surgical excision of 718 non-palpable breast lesions. Forty-two pathologists from 10 departments of pathology (generalists) made a diagnosis on both the needle and open biopsy specimens. Afterwards, three pathologists and two r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 10 publications
4
31
1
Order By: Relevance
“…Such major discrepancies might have serious impact on the therapeutic decisions made for individual patients in the sense of failing to diagnose invasive cancer or diagnosing a benign lesion as malignant and performing unnecessary surgical excision. The frequency of these major discrepancies was quite low and seemed to be independent on the type of specimen (NCB versus surgical excision) as reported by Verkooijen et al [15], who found a similar incidence of major discrepancies in large-core needle biopsy specimens and open breast biopsies.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Such major discrepancies might have serious impact on the therapeutic decisions made for individual patients in the sense of failing to diagnose invasive cancer or diagnosing a benign lesion as malignant and performing unnecessary surgical excision. The frequency of these major discrepancies was quite low and seemed to be independent on the type of specimen (NCB versus surgical excision) as reported by Verkooijen et al [15], who found a similar incidence of major discrepancies in large-core needle biopsy specimens and open breast biopsies.…”
Section: Discussionsupporting
confidence: 66%
“…Percentages of "false negative" and "false positive" diagnoses are reported in bold practice, the level of overall interobserver reproducibility could be higher than that reported in the present study. The COBRA study [15] assessed the interobserver variability between general and expert pathologists in a large series of large-core needle and open biopsies of non palpable breast lesions. In this study, pathological lesions were classified into five categories that do not exactly correspond to B-classification, even if a borderline category is reported that can be considered similar to B3 category of the B-classification.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly conflicting results have been reported for the association of HER2 expression, p53 mutations, tumor grade, bcl-2 and proliferation rate with response to primary chemotherapy [31,[34][35][36][37][38]. Differences in tissue fixation, staining methods, analytic criteria and interobserver variability among pathologists surely account for some of these disparate results [39][40][41]. Similarly, we could not identify any CDUS or PET imaging parameter that reliably predicted response.…”
Section: Discussioncontrasting
confidence: 73%
“…For CNB, inter-observer agreement has not been extensively investigated. Two studies of considerable size conclude that there is a high inter-observer agreement, although it seems likely that all participating pathologists had an 'above average' experience interpreting CNB specimens [33,34].…”
Section: Inter-observer Variabilitymentioning
confidence: 99%